Species composition of macrozoobenthos in lagoons of Sakhalin Island - Vjacheslav S. Labay (Известия ТИНРО, 2015)
Species composition of macrozoobenthos in lagoons of Sakhalin Island (in total, 637 species) is described on the base of cited data and results of author’s surveys. Its species composition is formed under influence of wide spectrum of environmental factors, as size of lagoon, water salinity, periodicity of connection with the sea and type of the water exchange, river discharge regime, climatic and geographical isolation, etc. Generally, 6 types of lagoons are determined on the coast of Sakhalin differed by composition of benthic fauna: 1) large semiclosed salty lagoon (Lake Busse in southern Sakhalin); 2) small semiclosed salty lagoons with water stratification and periodic connection with the sea (Lake Izmenchivoe and Lake Ptichye in southern Sakhalin); 3) large shallow semiclosed lagoons (in northern Sakhalin); 4) small isolated brackish lagoon (Kuegda Bay in northern Sakhalin); 5) closed oligosaline lagoons (Lake Tunaicha and Lake Aynskoe in southern Sakhalin); 5) isolated freshwater lagoons (Vavaysko-Chibisanskaya lake system in southern Sakhalin). Salty and freshwater lagoons are distinguished by the highest species diversity.